The Optimistic versus Pessimistic Life Plan Approach : Young adults' risk perceptions towards the life course in the USA and East Germany - Barabasch, Antje [Verfasser] (My University, 2008)
"The transition from school to work differs between East Germany and the United States of America. A strong regulation in one country and long orientation periods in the other are shaped by individual attitudes, beliefs, and values, and also by influences of parents, teachers, and peers as well as the economic situation in a country or region. This chapter introduces jour biographies four young adults from both countries and describes how various transitions take place. While the effects of globalization, such as a higher demand for flexible workers, are influencing young adults in both countries and the ideas of a patchwork biography where one pursues several careers over a lifetime are converging, approaches towards career and life planning processes as well as career aspirations are diverging." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 2.4.2 Lebenskonzepte, -stile, Werte; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1.1 Neue Bundesländer; I 2.3.2 Nordamerika; Berufseinmündung; Erste Schwelle; Lebensplanung; Wertorientierung; Risiko; Internationaler Vergleich; Ostdeutschland; USA